Research priorities for childhood chronic conditions: a workshop report. Issue 3 (2nd October 2018) - Lopez-Vargas, Pamela; Tong, Allison; Crowe, Sally; Alexander, Stephen I; Caldwell, Patrina Ha Yuen; Campbell, Dianne E; Couper, Jennifer; Davidson, Andrew; De, Sukanya; Fitzgerald, Dominic A; Haddad, Suzy; Hill, Sophie; et al.
Abstract : Background: Chronic conditions are the leading cause of mortality, morbidity and disability in children. However, children and caregivers are rarely involved in identifying research priorities, which may limit the value of research in supporting patient-centred practice and policy. Objective: To identify priorities of patients, caregivers and health professionals for research in childhood chronic conditions and describe the reason for their choices. Setting: An Australian paediatric hospital and health consumer organisations. Methods: Recruited participants (n=73) included patients aged 8 to 14 years with a chronic condition (n=3), parents/caregivers of children aged 0 to 18 years with a chronic condition (n=19), representatives from consumer organisations (n=13) and health professionals including clinicians, researches (n=38) identified and discussed research priorities. Transcripts were thematically analysed. Results: Seventy-eight research questions were identified. Five themes underpinned participants' priorities: maintaining a sense of normality (enabling participation in school, supporting social functioning, promoting understanding and acceptance), empowering self-management and partnership in care (overcoming communication barriers, gaining knowledge and skills, motivation for treatment adherence, making informed decisions, access and understanding of complementary and alternative therapies), strengthening ability to cope (learning to have a positive outlook, preparing for home care management, transitioning to adult services), broadening focus to family (supporting sibling well-being, parental resilience and financial loss, alleviating caregiver burden), and improving quality and scope of health and social care (readdressing variability and inequities, preventing disease complications and treatment side effects, identifying risk factors, improving long-term outcomes, harnessing technology, integrating multidisciplinary services). Conclusion: Research priorities identified by children, caregivers and health professionals emphasise a focus on life participation, psychosocial well-being, impact on family and quality of care. These priorities may be used by funding and policy organisations in establishing a paediatric research agenda.